Intensitas Perencanaan Strategik atas Teknologi Informasi untuk Meningkatkan Perekonomian Indonesia (Studi pada Perbankan di Indonesia) - Riana Dewi (Jurnal Akuntansi dan Bisnis, 2011)
The problem formulation of this research is does managerial factor, environment factor, organizational factor and technology give influence, either alone or together, toward the intensity of strategy planning and financial work”.The objective of this research is to give empirical evidence of the influence of managerial, environment, organizational and technological factors toward the intensity strategy planning and the influence of those factors above toward the financial work of Bank Perkreditan Rakyat (BPR). The analysis tools that are used are : classic assumption dan hypothesis test with path analysis. Result of this research that factor of manajerial with confidence, experience and membership influence strategic planning intensity. Environmental factor also considered strategic in the plan BPR. The environmental factor is also considered, because can have an effect on to performance. Factor of organisasional although have an effect on to strategic planning intensity of BPR and still got mixed up with less than 3 band off is effort. Organizational culture have influenced strategic planning, although the mentioned do not influence performance of finansial. Technological factor not yet influenced strategic planning intensity and performance of finansial, although BPR have started to make software and hardware with invesment which by dozens and always improve ability of the human resource. To the number of factor related to performance of finansial do not then express that strategic BPR in the plan unfavourable him. Emulation between BPR alone, other financial institution like co-operation, BMT, BKK, Bank Local government and Public Bank with is same product partake to play a part in to degrade performance of finansial BPR. Result of research also express that there are influence by together factor of manajerial, environmental, organisasional, and technology to performance of finansial. As a whole result of this research less is supporting of research conducted by Hopkins and Hopkins (1997), Rokhlianasari (2002), and Sudarmadi ( 2006) at factor of kontinjensi that is manajerial, environmental, and organizational to strategic planning intensity and performance of finansial. Suggestion to all manager to be earning open in reporting its activity. Because of researcher of difficulty in getting sampel caused by carefulness and policy of party of BPR so that represent limitation in this research. Amount of sampel hence result of research not yet earned to be told can deputize the overall of sampel because its minim of sampel in this research.